VR Technologies in Cultural Heritage First International Conference, VRTCH 2018, Brasov, Romania, May 29-30, 2018, Revised Selected Papers - Duguleană, Mihai; Carrozzino, Marcello; Gams, Matjaž; Tanea, Iulian (Communications in Computer and Information Science, 2019)
This open access book constitutes the refereed proceedings of the First International Conference on VR Technologies in Cultural Heritage, VRTCH 2018, held in Brasov, Romania in May 2018. The 13 revised full papers along with the 5 short papers presented were carefully reviewed and selected from 21 submissions. The papers of this volume are organized in topical sections on data acquisition and modelling, visualization methods / audio, sensors and actuators, data management, restoration and digitization, cultural tourism.